Peningkatan Hasil Belajar IPS dengan Metode Problem Solving di Sekolah Dasar - Ermisusanti, Eka; Zuardi, Zuardi; Ahmad, Syafri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The purpose of this study is to describe the improvement of IPS learning outcomes by using Problem Solving method in class IV SDN 04 2x11 EnamLingkung. The type of research is class action research, using qualitative and quantitative approach, done with two cycles that is cycle I and cycle II. Increased: at planning 69,65% to 92,57%, teacher aspects 72,09% to 87,6%, student aspect 70% to 88,6%. It can be concluded that problem solving method can improve student learning result of IPS. Keywords: Problem solving; IPS learning outcomes